1985
DOI: 10.1007/bf00380963
|View full text |Cite
|
Sign up to set email alerts
|

Childhood experiences of endogenous and neurotic depressives

Abstract: The parent-child relationship, the relationship between the parents, and the contact of the child with the outside world was investigated on the basis of retrospective interview data concerning the childhood of endogenous and neurotic depressives and a nonclinical control group. A number of significant links between childhood experiences and the various forms of depression emerges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In the course of this study, crossvalidated results in several countries (48) have shown (consistent with the results of an independent study by Matussek et al (49)) that depression-prone individuals, compared with healthy controls, have experienced their parents as lacking emotional warmth (and, albeit to a lesser extent, as rejecting). Table 1 shows the results from a few countries.…”
Section: Attitudes Towards Child-rearing: a Possible Early Interactiosupporting
confidence: 90%
“…In the course of this study, crossvalidated results in several countries (48) have shown (consistent with the results of an independent study by Matussek et al (49)) that depression-prone individuals, compared with healthy controls, have experienced their parents as lacking emotional warmth (and, albeit to a lesser extent, as rejecting). Table 1 shows the results from a few countries.…”
Section: Attitudes Towards Child-rearing: a Possible Early Interactiosupporting
confidence: 90%
“…Yet another influence on the child's potential future depression is the gender of the psychologically unavailable or affectionless controlling parent and the child. While most of the studies reported here have pointed to the mother as the more influential parent (Main et al, 1985;Parker, 1979Parker, , 1982Parker, , 1983Parker & Had&Pavlovic, 1984), this pattern has not been wholly consistent, with some studies finding paternal caring (Parker & Lipscombe, 1980), the same-sex parent (Matussek et al, 1985), or both parents (Blatt et al, 1991;Johnson et al, 1982;McCranie & Bass, 1984) to be primary, and others, such as the studies of depressed mothers, not examining the father's role at all. The model of psychological development proposed by Blatt and Shichman (1983) suggests that girls' developmental demand for a shift in the attachment of affection from mother to father in early childhood and boys' deveIopmenta1 demand for a shift in identification from mother to father in early childhood could account for the differential tendency for females to become more often depressed around interpersonal issues (i.e., dependency) and for males to become more often depressed around issues of self-de~nition (i.e., self-criticism).…”
Section: Discussionmentioning
confidence: 58%
“…Self-critical 12-year-old boys, however, tended not to be still self-critical at 31 years, but reported greater experience of aggressive impulses, though not of aggressive actions. Matussek et al (1985), in differentiating various diagnostic groupings of depression, describe two kinds of childhood experiences that correspond roughly to the anaclitic/ introjective distinction. They found that of former inpatients who had been diagnosed as neurotically depressed, women felt that as children they received little attention from their mothers and little appreciation from their fathers, while men reported feeling distant from their fathers.…”
Section: Mccraniementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study (3) male and female depressive patients were analyzed separately. Female depressives as a whole did not differ significantly from controls regarding parent-child relationship, the relationship between parents, or the child's contact with the outside world.…”
mentioning
confidence: 99%